Leveraging migration for Africa: remittances, skills, and investments - Ratha, Dilip (Washington, World Bank, 2011)
A joint effort led by the African Development Bank and the World Bank, 'Leveraging Migration for Africa' is the first comprehensive publication on harnessing migration, remittances, and other diaspora resources for the development of Africa. It comes at a time when countries in Africa and elsewhere are grappling with difficult choices on how to manage migration. Policy makers can help leverage the contributions of migrants to the development of Africa, reduce remittance costs, improve the efficiency of remittance markets in both origin and destination countries, and address the needs of the origin countries without restricting the emigration of high-skilled professionals. Innovative financing mechanisms such as issuance of diaspora bonds and securitization of future remittance flows can help finance big-ticket projects, such as railways, roads, power plants, and institutions of higher learning that will, step by step, help to transform Africa. This volume contributes to a greater understanding of migration and its potential role in Africa?s development
Keywords: Africa Emigration and immigration Economic aspects; POLITICAL SCIENCE Public Policy Economic Policy